Quinine and mefloquine in the treatment of multidrug-resistant Plasmodium falciparum malaria in pregnancy. - Mcgready, R; Cho, T; Hkirijaroen, L; Simpson, J; Chongsuphajaisiddhi, T; White, N; Nosten, F (1998)
Between 1991 and 1996, 372 pregnant women with uncomplicated, multidrug-resistant Plasmodium falciparum malaria, living on the western border of Thailand, were treated with either mefloquine (N = 194), quinine (N = 93) or both drugs (N = 85). Antimalarial treatment was generally well tolerated; the most common side-effects were dizziness (42%) and tinnitus (35%) following quinine, and anorexia (23%) and dizziness (36%) following mefloquine. In the patients treated for primary infections with melfloquine, 6% failed to clear their parasitaemia by day 7 and 28% failed by day 42. The corresponding figures for quinine were 4% and 23%, respectively. The failure rates in the 117 women treated for recrudescent infections were higher, the increase being significant for quinine (38%; P = 0.03) but not for mefloquine (37%). The percentage of pregnant women who had patent gametocytaemia on presentation ranged from 4%-19%. Over 50% of the patients were anaemic (haematocrit < 30%) on presentation and 52% of those not anaemic on enrolment developed anaemia during follow-up. Mefloquine and quinine, the only antimalarials generally available for the treatment of highly drug-resistant P. falciparum in pregnancy, give unsatisfactory treatment responses when used as single agents. New, safe and effective regimens are needed for the treatment of pregnant women with multidrug-resistant falciparum malaria.